THE FUNCTIONAL ROLE OF MELATONIN AND KISSPEPTIN IN FISH REPRODUCTION - Mondal, Pradip; Hira, Sumit Kumar; Saha, Nimai Chandra (Innovare Journal of Sciences, 2019)
Reproduction of fish generally governed by the counter interaction of some endogenous and exogenous cues like endocrine signals and one or more environmental factors such as photoperiod, temperature, rainfall, food availability, salinity etc. Study indicates that it depends on hypothalamo-hypophysis-gonadal axis. In gonad, gametogenesis is ordered by various hormones followed by their interactions with proper tissues leading to breed at a specific time of the year. Melatonin, a neuroendocrine hormone, has a significant physiological role in the regulation of seasonality and gonadal development of fish. On the other hand, receptor independent actions or free radical scavenging role of melatonin at different levels of hypothalamo-hypophysis-gonadal axis is not yet clear. In recent years, focus has been given to study the of kisspeptin peptides potentiality on gonadal development especially during the transitional period of puberty and gonadal relapse. The relationship of kisspeptin and gonadotropin-releasing hormone is a good illustration of the kisspeptin system. The role of kisspeptin and melatonin in the reproduction of fish is an important subject of research. The potency of kisspeptin and melatonin on reproductive maturation and gonadotropin release in response to environmental cues and the regulation of secretion of gonadotropin-releasing hormone by kisspeptin and melatonin are also the important objectives of the present review.